2012
DOI: 10.5121/ijma.2012.4412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Content Based Image Retrieval Systems Using Wavelet and Curvelet Transform

Abstract: The large numbers of images has posed increasing challenges to computer systems to store and manage data effectively and efficiently. This paper implements a CBIR system using different feature of images through four different methods, two were based on analysis of color feature and other two were based on analysis of combined color and texture feature using wavelet coefficients of an image. To extract color feature from an image, one of the standard ways i.e. color histogram was used in YCbCr color space and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…This is confirmed by the existence of a number of articles [26] [27] [28] [29] [30]. At the same time the HSV color system is preferable in implementing the contrast change procedure.…”
Section: Color System Hsv For Image Analysismentioning
confidence: 54%
“…This is confirmed by the existence of a number of articles [26] [27] [28] [29] [30]. At the same time the HSV color system is preferable in implementing the contrast change procedure.…”
Section: Color System Hsv For Image Analysismentioning
confidence: 54%
“…In 2012, Das et al [25] suggested a CBIR system that can apply on different feature of images. To focus shading highlights from a photo, one of the standard ways i.e.…”
Section: Related Workmentioning
confidence: 99%
“…With expansive information sets, there is probability of high dimensionality. In 2012, Das et al [26] implemented a CBIR system which uses different feature of images by applying four methods, two methods were based on the color feature analysis and rest two were based on color and texture feature analysis using wavelet coefficients of an image. In 2007, Jain et al [27] proposed an algorithm for retrieving images.…”
Section: Related Workmentioning
confidence: 99%